Collaborative work in the implementation of Industry 4.0 technologies and its relationship with business sustainability in an emerging economy - César A. Bernal-Torres; Luz Elba Torres-Guevara; Erick L. Álvarez-Aros; José L. Barrera-Canto; Ruth N. Ojeda-López (International Journal of Innovation Studies, 2025)
This study analyses the association between business sustainability and implementing Industry 4.0 through collaborative work and open innovation with stakeholders in medium and large companies in an emerging economy. The information was obtained from a sample of 165 executives from the same number of companies through a survey based on a Likert scale from 1 to 5. Data processing was conducted using the structural equation model (SEM). The results indicate that companies practice limited collaborative work with stakeholders and other societal actors to implement Industry 4.0 technologies. Despite this, there is evidence of an association between implementing these technologies and business sustainability. The results confirm the findings of previous studies in companies in developed economies, where this relationship has become an excellent strategy to address the complex and uncertain challenges faced by companies today. Likewise, the study's results provide empirical evidence for managers in emerging economies to decide how to enhance their competitive capacity. Similarly, it provides new information to those responsible for public agencies in economic issues to design and guide public policy that contributes to improving business competitiveness.